Levels of physical activity in people living with chronic pain: Do they change after participating in a Chronic Pain Management Program? - Swartz, Damian (Department of Health and Rehabilitation Sciences, 2020)
Purpose: The purpose of this study was to determine whether levels of physical activity in people with chronic pain change after participating in a Chronic Pain Management Program (CPMP) at Groote Schuur Hospital (GSH). Methods: A pre-experimental pre-test, post-test study was conducted, consisting of 14 men and women suffering from chronic pain who were referred to a Chronic Pain Management Program (CPMP) from the Chronic Pain Management Clinic at GSH in Cape Town, South Africa. Subjective and objective measuring tools, including pedometry, were used to collect data and non-parametric analysis was conducted to analyse data. Results: 14 participants met the Inclusion criteria. Levels of physical activity changed markedly, but not significantly. Objectively-tested and self-reported physical activity levels changed significantly among participants who took part in a CPMP. Significant improvements in Pain Severity Scores and Pain Interference Scores occurred after the CPMP and there was convergent validity between self-reported and objectively-tested levels of physical activity in those suffering from chronic pain after the CPMP. Conclusion: The Chronic Pain Management Program at Groote Schuur Hospital in Cape Town has shown to improve function and physical activity of those patients living with chronic pain who take part in the CPMP, with function improving significantly, and physical activity nearly doubling in the group being tested who took part in the 5-week long program. The CPMP at GSH should be seen as the beginning of a greater movement towards increasing physical activity in the chronic pain sphere. Research in more public healthcare facilities is needed to increase knowledge around education, pacing and implementation strategies across South Africa.